2011
DOI: 10.1002/hep.24416
|View full text |Cite
|
Sign up to set email alerts
|

A key role for Pre–B cell colony–enhancing factor in experimental hepatitis

Abstract: Pre-B cell colony-enhancing factor (PBEF), also known as nicotinamide phosphoribosyltransferase or visfatin, plays an important role in metabolic, inflammatory, and malignant diseases. Recent evidence suggests that blocking its enzymatic activity using a specific smallmolecule inhibitor (FK866) might be beneficial in acute experimental inflammation. We investigated the role of PBEF in human liver disease and experimental hepatitis. PBEF serum levels and hepatic expression were determined in patients with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…FK-866 has been tested in spinal cord injury and experimental hepatitis in in vitro and in vivo models. FK-866 administration results in iNAD depletion and reduced proinflammatory cytokine expression (12,13). Although the extracellular proinflammatory effects of NAMPT/PBEF are well studied, little is known regarding how intracellular iNAMPT enzymatic activity contributes to ARDS pathogenesis.…”
Section: Clinical Relevancementioning
confidence: 99%
“…FK-866 has been tested in spinal cord injury and experimental hepatitis in in vitro and in vivo models. FK-866 administration results in iNAD depletion and reduced proinflammatory cytokine expression (12,13). Although the extracellular proinflammatory effects of NAMPT/PBEF are well studied, little is known regarding how intracellular iNAMPT enzymatic activity contributes to ARDS pathogenesis.…”
Section: Clinical Relevancementioning
confidence: 99%
“…As a result, LPS-induced mRNA up-regulations of pro-inflammatory cytokines were attenuated by co-administration of visfatin antagonist (FK-866), suggesting that visfatin plays some roles in the enhanced inflammatory responses of WAT in OVX rats. It has been reported that, as noted above, visfatin induces the anorectic and febrile responses and plays a key role in experimental hepatitis in rodents [4,6]. We have previously reported that OVX female rats exhibited stronger anorectic and febrile responses than sham female rats [10].…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that visfatin plays roles in immune responses in both chronic and acute inflammatory conditions [1][2][3][4][5][6]. Visfatin transcription is regulated by interleukin (IL)-6, tumor necrosis factor (TNF), and glucocorticoids in adipose tissue, and it is also produced in neutrophils [5,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interrelation between visfatin/NAMPT and inflammation is also supported by the observation that the synthesis of visfatin/NAMPT-like proinflammatory cytokines is upregulated in a wide range of inflammatory states such as inflammatory bowel diseases [27], arthritis [28], psoriasis [29], atherosclerosis [30], chronic obstructive pulmonary disease [31], and even pneumonia [32] or hepatitis [33]. In line with these findings, Carrero et al [34] demonstrated increased visfatin/NAMPT levels in stage 5 CKD patients with poor appetite, which is one of the signs associated with chronic inflammation.…”
Section: Discussionmentioning
confidence: 89%